2014
DOI: 10.1007/s00468-014-1143-6
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific variation of anatomical and chemical defensive traits in Maritime pine (Pinus pinaster) as factors in susceptibility to the pinewood nematode (Bursaphelenchus xylophilus)

Abstract: Key message Migration ability of the PWN through wood branch tissues of adult Maritime pine trees significantly differed among Iberian provenances and this variation was related to differences in anatomical and chemical defensive traits. Abstract The pinewood nematode or pine wilt nematode (PWN; Bursaphelenchus xylophilus) is one of the most dangerous threats to European coniferous forests, especially for the susceptible Maritime pine (Pinus pinaster), a valuable forest resource in South Western Europe. The PW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
22
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 57 publications
5
22
1
2
Order By: Relevance
“…This included terpenoids, both constitutive and induced, of which resin is comprised. Similar results were obtained by Zas et al () with Pinus pinaster . Constitutive and induced starches, sugars, and phenolics were highly variable and likewise did not exhibit clear patterns.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This included terpenoids, both constitutive and induced, of which resin is comprised. Similar results were obtained by Zas et al () with Pinus pinaster . Constitutive and induced starches, sugars, and phenolics were highly variable and likewise did not exhibit clear patterns.…”
Section: Discussionsupporting
confidence: 91%
“…In some instances, resin ducts have been related to tree survival to bark beetles, with larger size and higher numbers having stronger relationships with survival (Ferrenberg, Kane, & Mitton, ; Hood, Sala, Heyerdahl, Boutin, & Raffa, ; Kane & Kolb, ). These processes have linkages, in that resin cells extend throughout the plant to produce and deliver chemicals in attacked tissues (Björkman, Larsson, & Gref, ; Zas et al, ). Although some studies examined both anatomical and chemical components of tree defence (Bentz, Hood, Hansen, Vandygriff, & Mock, ), or within‐tree correlations within seedlings (Moreira, Zas, Solla, & Sampedro, ), to our knowledge, none have tested their relatedness within the same mature trees or compared relationships between species of different exposure histories.…”
Section: Introductionmentioning
confidence: 99%
“…Many pine species, especially those with isolated and fragmented small populations, harbour large intraspecific genetic variation, with high population differentiation in many different life‐history traits (Grivet et al ., ), including resistance to pathogens (e.g. Zas et al ., ). Specifically, resistance to F. circinatum is known to vary among populations in a wide array of pine species, including Pinus leiophyla (Dvorak et al ., ), P. patula (Hodge & Dvorak, ; Dvorak et al ., ), P. tecunumanii (Hodge & Dvorak, ; Dvorak et al ., ), P. oocarpa (Dvorak et al ., ) and Pinus pinaster (Iturritxa et al ., ; Elvira‐Recuenco et al ., ).…”
Section: Exploiting Genetic Resistance Against F Circinatummentioning
confidence: 99%
“…pinaster being the most susceptible and Pinus pinea as the most resistant species [107]. However, Zas et al [108] reported intraspecific variation in resistance to PWN in Pi. pinaster at the provenance level.…”
Section: Pinewood Nematodementioning
confidence: 99%